Parliament, the budget and gender (2004)
The purpose of this handbook is to make a contribution towards supporting parliamentarians to effectively participate in the budget process. An attempt is made to acknowledge the variety of national approaches and experiences. The general text in each chapter is complemented with case studies and examples to illustrate particular issues. We have attempted to be as diverse as possible in our choice of examples. In addition, the appendix contains a short budget glossary, suggestions for further reading, and a list of useful websites.